THE STUDENTSÃ¢â¬â¢ COMPETENCY IN WRITING DESCRIPTIVE PARAGRAPH AT ELECTRICAL AND MECHANICAL DEPARTMENT, FACULTY OF ENGINEERING, TRIDINANTI UNIVERSITY PALEMBANG - Rusman Roni (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
Abstract: The purpose of this study was to describe the studentsÃ¢â¬â¢ ability in writing descriptive paragraph at electrical and mechanical department. This study is descriptive in the sense that it aims at describing the knowledge and skill of electrical and mechanical department. The two kinds of data were correlated by applying the Spearman Rank Order Coefficient. The subjects of this study were 45 sample students selected from the students who attended English II at Faculty of Engineering, Tridinanti University. The general results indicate that the majority of the subjects were good at writing a descriptive paragraph. And it was also found that there were a relationship between the studentsÃ¢â¬â¢ knowledge of descriptive paragraph and their performance in writing descriptive paragraph at electrical and mechanical department, Faculty of Engineering, Unanti Palembang ( r=0,831). It implies that an increase in the knowledge in writing descriptive paragraph of the studentsÃ¢â¬â¢ score is accompanied by a corresponding increase in the skill of writing descriptive paragraph.